2006
DOI: 10.1007/s10582-006-0237-9
|View full text |Cite
|
Sign up to set email alerts
|

Energy distributions of particles ejected from laser-generated pulsed plasmas

Abstract: A study of laser ablation in vacuum of metallic elements (Al, Cu and Ta) at different boiling points is reported. A Nd:YAG laser radiation, 3 ns pulse duration and 10 9 W/cm 2 intensity, produces non-isotropic emission of neutral and ionic species. Mass quadrupole spectrometry, coupled to a 45 • electrostatic ion deflection, allows estimation of the energy distributions of the emitted species within the plasma plume as a function of the incident laser energy. Neutrals show typical Boltzmann distributions indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
4
5
0
Order By: Relevance
“…8 were identified according to the NIST database. As can be seen, Al + was the main Al charge state, which corresponded to the results reported by Caridi et al [31]. Therefore, the Al + whose spectral line appeared at the wavelength of 624.33 nm could be selected as the representative species to analyze the ion plume images.…”
Section: Figuresupporting
confidence: 81%
See 1 more Smart Citation
“…8 were identified according to the NIST database. As can be seen, Al + was the main Al charge state, which corresponded to the results reported by Caridi et al [31]. Therefore, the Al + whose spectral line appeared at the wavelength of 624.33 nm could be selected as the representative species to analyze the ion plume images.…”
Section: Figuresupporting
confidence: 81%
“…The emission intensity was more distinguished for the condition of a fluence higher than 15.92 J/cm 2 . This could be interpreted with the result of [31] that the charges state increased with the laser fluence and the energetic distributions shifted towards higher energies. Additionally, with the increase of the laser fluence, the highest radiation intensity region in the plasma plume located above the target surface was observed, and it was called the plasma core [17].…”
Section: Figurementioning
confidence: 60%
“…Figure 3 decrease in the mean ion energy as a function of emission angle for all the investigated charge states and laser power densities. This is in agreement with previous charge-integrated results presented by Hansen et al 32 (1-4 Â 10 11 W/ cm 2 ) and Claeyssens et al 33 performed on Ag and C, respectively, and with charge-differentiated results presented by Caridi et al 34 for Ta ions with a laser power density in the region of 10 9 W/cm 2 . Investigating the mean ion energy as a function of ion charge for a range of emission angles, from Fig.…”
Section: A Energy Distributionsupporting
confidence: 93%
“…Ions traversing the double layer are reported to gain a substantial fraction of their final kinetic energy. 34,35,55,58 Bulgakova et al examined the angular distribution of ions due to the formation of a double layer within a plasma plume, for similar spot size conditions to those employed in this study, and found ions subjected to potential acceleration are ejected in a narrow emission cone. 35,62 The introduction of a Knudsen and/or a double layer superimposed on the supersonic adiabatic expansion of the plume can help further describe the features observed in this study.…”
Section: B Double Layermentioning
confidence: 82%
“…Tantalum (Ta) plates were used as target samples. They exhibit low ablation threshold in comparison with other metals [23][24][25], which enables us to perform ablation experiment easily. Thickness of the Ta plates was ~1 mm and the plate surfaces were polished by sandpaper.…”
Section: Methodsmentioning
confidence: 99%